New monoterpenes from stalks and infructescence of Sibiraea leavigata. (December 2016) - Zhao, Jian-Qiang; Wang, Yan-Ming; Lv, Jun-Jiang; Wang, Shuo; Mei, Li-Juan; Tao, Yan-Duo
Graphical abstract: Highlights: Two new monoterpenes named sibiscolactons A and B (1 and2 ) were isolated from Sibiraea laevigata . New compounds' absolute configurations were established by electronic circular dichroism (ECD) calculations. Eight known phenylpropanoids (3 –10 ) were also obtained from the title plant. 1 –10 were evaluated for their cytotoxic activity. Compound3 displayed moderate cytotoxicity with IC50 values ranging from 10.8 to 49.2 μg mL −1 . Abstract: Chemical investigation of the ethanol extract of the stalks and infructescence of Sibiraea leavigata led to the isolation of two new monoterpenes named (4 R )-2-(2-hydroxy-4-methyl-3-pentenyl)furan-2(5 H )-one (1 ) and (2 R, 4 R )-2-(2-hydroxyethyl)-4-(2-methyl-1-propenyl)furan-5 H -2-one (2 ) along with eight known phenylpropanoids (3–10 ). Their structures were established on the basis of the interpretation of spectroscopic data and electronic circular dichroism (ECD) calculations. In addition, all of these isolates were evaluated for their cytotoxic activity. The results showed that compound3 displayed moderate cytotoxicity with IC50 values ranging from 10.8 to 49.2 μg mL −1 against five cell lines. While1 showed selective promotion effects on proliferation of gastric cancer MGC803 and RSC96 cell lines.